Analisis Spasial Tempat Perindukan Nyamuk, Kepadatan Larva dan Indeks Habitat dengan Kejadian Malaria di Kecamatan Waigete Kabupaten Sikka - Romualdus Suyono; Johny A. R. Salmun; Honey I. Ndoen (Universitas Nusa Cendana, 2021)
Waigete sub-district is a malaria endemic area, so an effective and efficient vector control strategy is needed. Spatial analysis is the general ability to compile and process spatial data into a variety of different forms in such a way as to provide new or additional meanings. This study aims to spatially analyze the types, types, positive breeding places for larvae and larvae density as well as the habitat index with the incidence of malaria in Waigete District in 2019/2020. This type of research is a descriptive observational study with a cross-sectional approach. The population in this study were 39 patients and 53 breeding points with saturated sampling technique. The analysis showed that there were 53 breeding points with nine types, namely lakes, reservoirs, ditches, rice fields, springs, ponds, lagoons, rivers and puddles, malaria cases totaled 39 cases. There is a distribution pattern of breeding places that are close to malaria sufferers with a radius of less than 500 m, there is a high larval density in the Waigete sub-district. The spread of breeding places and positive malaria cases occur at altitudes below 700 mdpl. Communities need to work together to manipulate and modify, clean up breeding places for mosquitoes, and sow biological predators in all breeding places for mosquitoes.